Advances in Stored Product Protection. Proceedings of the 8th International Working Conference on Stored Product Protection, Yo 2003
DOI: 10.1079/9780851996912.0588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NeemAzal and other neem products on mortality, fecundity and frass activity of the larger grain borer Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae) infesting maize.

Abstract: Two NeemAzal products from Trifolio GmbH, Germany, and neem oil and neem seed cake powder of the Kenyan neem tree were tested for their efficacy against the storage pest P. truncatus in the laboratory at (a) low, (b) medium and (c) high rates, containing approximately 1.5, 3 and 6 mg azadirachtin A/kg maize, respectively. The maize samples were stored in 250 ml glass jars at 30°C and 70% relative humidity. After one month of storage, NeemAzal PC KG 01 (0.1% azadirachtin A) at all the tested rates and neem seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…The toxic action of NSP and P. glandulosus powder was slower than that of NeemAzal powder and NSO. Our result on the insecticidal efficacy of NeemAzal against S. zeamais is different from that of Ogemah et al (2002). These authors reported that at the rate of 6 g/kg, NeemAzal powder caused complete mortality of P. truncatus on maize within 28 days, while in our study it caused 98% mortality of S. zeamais within 14 days.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The toxic action of NSP and P. glandulosus powder was slower than that of NeemAzal powder and NSO. Our result on the insecticidal efficacy of NeemAzal against S. zeamais is different from that of Ogemah et al (2002). These authors reported that at the rate of 6 g/kg, NeemAzal powder caused complete mortality of P. truncatus on maize within 28 days, while in our study it caused 98% mortality of S. zeamais within 14 days.…”
Section: Discussioncontrasting
confidence: 84%
“…These results are similar with the findings of other workers. NeemAzal powder, NSO and NSP inhibited F 1 progeny of P. truncatus (Ogemah et al 2002). Crude powders from Lantana camara and Tephrosia vogelii reduced F 1 progeny of S. zeamais by over 75% (Ogendo et al 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation